People's Republic of China : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the People's Republic of China. (International Monetary Fund, 2021)
The Chinese economy continues its fast recovery from the health and economic crisis as a strong containment effort and macroeconomic and financial policy support have mitigated the crisis impact and helped the economy rebound. However, growth is still unbalanced as the recovery has relied heavily on public support while private consumption is lagging. Rising financial vulnerabilities and the increasingly challenging external environment pose risks to the outlook. Important reforms have progressed despite the crisis, but unevenly across key areas.